Fast Check for Block Shear - Burgett, Lewis B. (Engineering Journal, 1992)
Block shear is a fracture type failure in which fracture may occur either along the shear plane or along the tension plane (see Fig. 1). The first plane to reach its fracture strength will not fail (separate) but is restrained by the stronger plane until the fracture strength of the second is reached. Just before fracture along the stronger plane the total strength will be the sum of the fracture strength along the stronger plane plus the yield strength of the weaker plane.